Evaluasi Sistem Pendidikan Tentang Penerapan Deep Learning Di SMA Al-Anshar Tanjung Selor - Hasmawati; Aminullah; Wardana (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to evaluate the education system related to the independent curriculum with the application of a deep learning approach at Al-Anshar Tanjung Selor High School, Bulungan Regency, by examining the suitability between the goals of national education and its implementation. Data collection is carried out through the literature research method. The research focuses on the evaluation of the education system by examining various literature such as books, notes, and previous research reports where the implications of the independent curriculum policy with a deep learning approach are the main source of information in this research is the policy of the deep learning approach in learning published by the Ministry of Primary and Secondary Education. and other relevant sources to dig up information related to the deep learning approach model. The results of the study show that deep learning has not been fully applied in the upper secondary education unit, but there are efforts and efforts because the deep learning approach in learning has a very important role in ensuring the success and smoothness of every learning. This is done by teachers as educators. To identify students who are able to receive the material taught through the deep learning approach, teachers must be able to design so that students are no longer saturated, bored, ignorant and not enthusiastic but more aware, meaningful and encouraging. This research shows a very close relationship in the current curriculum.